Transformasi Penerapan Aspek Green Accounting Sebelum dan Saat Pandemi Covid-19 (Pada Perusahaan Manufaktur dan Pertambangan Yang Terdaftar Di BEI): Disclosure of Environmental Performance, Environmental Costs, Environmental Disclosure, Environmentally Friendly Products, Environmental Activities, Environmental Audit - Ni Luh Indrawati; Devi, Sunitha (Vokasi : Jurnal Riset Akuntansi, 2022)
This study aims to determine the transformation of the application of green accounting aspects before and during the Covid-19 pandemic in manufacturing and mining companies listed on the Indonesia Stock Exchange. Then the green accounting aspect with environmental performance, environmental costs, environment, environmentally friendly products, environmental activities, and audits. This type of research is quantitative research. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange as many as 154 companies, and the population of mining companies as many as 40 companies. The sample of this study was determined by purposive sampling technique by determining the sample, namely manufacturing and mining companies listed on the IDX during the 2018 and 2020 periods, companies that have annual reports and the 2020 period and companies that are consistently responsible for the 2018 and 2020 social periods, so that the obtained a sample of 19 manufacturing companies and 8 mining companies. Data analysis using Wilcoxon Signed Rank Test. Data analysis using the SPSS 25 application. The results showed that: (1) there was a significant difference in environmental performance between before and during the Covid-19 pandemic, (2) there was no significant difference in environmental costs between before and during the Covid-19 pandemic. 19 -19, (3) there is a significant difference in the environment between before and during the Covid-19 pandemic, (4) there is no significant difference in environmentally friendly products between before and during the Covid-19 pandemic, (5) there is no significant difference significant difference in environmental activities between before and during the Covid-19 pandemic, and (6) there is no significant difference in environmental audits between before and during the Covid-19 pandemic